The progress principle : using small wins to ignite joy, engagement, and creativity at work - Kramer, Steven, ....-; Amabile, Teresa, ....- (Boston : Harvard Business Review Press, 2011)
What really sets the best managers above the rest? It's their power to build a cadre of employees who have great inner work lives--consistently positive emotions; strong motivation; and favorable perceptions of the organization, their work, and their colleagues. The worst managers undermine inner work life, often unwittingly. As Teresa Amabile and Steven Kramer explain in The Progress Principle, seemingly mundane workday events can make or break employees' inner work lives. But it's forward momentum in meaningful work--progress--that creates the best inner work lives. Through rigorous analysis of nearly 12,000 diary entries provided by 238 employees in 7 companies, the authors explain how managers can foster progress and enhance inner work life every day. The book shows how to remove obstacles to progress, including meaningless tasks and toxic relationships. It also explains how to activate two forces that enable progress: (1) catalysts--events that directly facilitate project work, such as clear goals and autonomy--and (2) nourishers--interpersonal events that uplift workers, including encouragement and demonstrations of respect and collegiality. Brimming with honest examples from the companies studied, The Progress Principle equips aspiring and seasoned leaders alike with the insights they need to maximize their people's performance.